PERAN GURU BK DALAM DALAM PENCEGAHAN PERUNDUNGAN DIGITAL: SEBUAH SYSTEMATIC LITERATURE REVIEW - M Khairudin; Defriyanto Defriyanto; Laila Maharani (STKIP Pesisir Selatan, 2026)
Cyberbullying is one of the serious issues in the field of education that significantly impacts students’ psychological, social, and academic well-being. Along with the increasing use of digital technology, schools are required to develop systematic and sustainable prevention strategies. This study aims to comprehensively examine cyberbullying prevention strategies discussed in various studies and to analyze how these strategies can strengthen the role of school counselors. The method used is a Systematic Literature Review by examining relevant scientific articles that were systematically selected based on specific criteria. The synthesis results indicate that cyberbullying prevention strategies include relational, psychological, educational, technological, and school policy approaches. The main findings reveal that school counselors play a strategic role in fostering school connectedness, enhancing empathy, strengthening digital literacy, and providing preventive psychosocial support. However, this role has not yet been fully optimized in school practice and policy. This study concludes that strengthening the role of school counselors is a key element in creating an effective and sustainable cyberbullying prevention system within the educational environment.